Effect of Cl/S and Na interaction on ash deposition mechanism at the inlet of Shell gasifier syngas cooler - Xingrui CAI; Yuefeng WANG; Yujia DU; Haotian XUE; Chong HE; Yuexing WEI; Xiaojiao LI; Yuhong QIN; Baoming ZHAO (Meitan xuebao, 2024)
The Shell dry pulverized coal pressurized gasification is one of the important technologies for the clean and efficient utilization of coal. Ash deposition at the inlet of the syngas cooler caused by alkali metal compounds is the main reason for the unscheduled shutdown of the gasifier. The effect of Cl/S and Na interaction on ash deposition is studied by adding different contents of Na, Cl and S to the raw fly ash. The ash deposition experiment is conducted by using the deposition probe in the self-built high temperature vertical furnace. The ash deposition behavior is studied by separating it into inner layer and the outer layer. The mass changes of the inner and outer ash deposits are discussed. The physicochemical properties of the inner and outer ash deposits are compared and analyzed by means of ICP-MS, IC, SEM-EDS and XRD. The influence of the interaction among elements such as Cl, S and Fe on the ash deposition behavior is obtained. The results show that the mass of inner ash deposits increases with time. The addition of compounds containing S reduces the mass of both the inner and outer ash deposits. And the mass of outer ash deposits decreases with time. The Na in the form of aluminosilicate promotes the growth of ash deposit in the outer layer. The Cl is enriched in the initial viscous layer in the form of alkali metal chloride. The existence of S slows down the pipeline dust deposition. In the presence of Cl and S, the Fe reacts with Si, Al and Na and generates a variety of low temperature eutectic, promoting the melting of inner and outer ash deposition. The formation mechanism of ash deposit at the inlet of the Shell gasifier syngas cooler is as follows: firstly, under the interaction among the Na, Cl, Si and Al, the alkali metal chloride and aluminosilicate deposit in the inner layer. At the same time, the existence of Cl and S combine with Fe and Na to form Fe-O-Si, Fe-O-S and Fe-Na-O-Al-S eutectic. Then, the melting of aluminosilicate and various low temperature eutectic increase the size of ash particles and promote the further growth of ash deposition.